Femoral neck fractures treated with cannulated screws: can surgeons predict functional outcomes and minimize the risk of necrosis? - De Franco, Silvia; Ipponi, Edoardo; Ruinato, Alfio Damiano; Parchi, Paolo Domenico; Andreani, Lorenzo; Scaglione, Michelangelo; Capanna, Rodolfo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Femoral neck fractures are among the most frequent in mankind. Screw fixation is considered a suitable approach specially for undisplaced or slightly displaced fractures that occur to young patients. We conducted our study in order to evaluate both functional outcomes and complication rates of patients who received this treatment in our institution. A particular focus was given to the aseptic necrosis of the head, trying to identify if anamnestic, clinical or radiological data could play a significant role as prognostic factors. Methods: For each case who was treated with screw fixation due to a femoral neck fracture, we recorded data regarding, among the others, BMI and whether they used tobacco products or corticosteroids on a regular basis. Necrosis of the femoral head and mechanical complications were recorded. Functional outcome was evaluated using the Harris Hip Score. Results: 74 cases were included in our study. The mean Harris Hip score was 89.5. Aseptic necrosis of the femoral head occurred in 9 cases (12.2%). Regular use of tobacco was associated with a higher risk to develop necrosis (p=0.007). The Body Mass Index was significantly higher in cases who had necrosis compared to the rest of our population (p=0.043) and was inversely proportional to the post-operative Harris hip score (p=0.001). Conclusions: While considering screw fixation to treat cases with femoral neck fractures, patient’s weight and use of tobacco should be considered as prognostic factors. (www.actabiomedica.it)